2011
DOI: 10.1007/s12010-011-9351-7
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-Induced Cellular and Molecular Events Are Responsible for Productivity Enhancement in Hairy Root Cultures: An Insight Study

Abstract: A wide range of external stress stimuli triggers a plant cell to undergo a complex network of reactions that ultimately lead to the synthesis and accumulation of secondary metabolites. These secondary metabolites help the plant to survive under stress challenge. The potential of biotic and abiotic elicitors for the induction and enhancement of secondary metabolite production in various culture systems including hairy root (HR) cultures is well-known. The elicitor-induced defense responses involves signal perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 90 publications
0
26
0
Order By: Relevance
“…), microorganisms (chitin, glucans, etc. ), and G proteins which are bound to the receptors and act by activating or inactivating ion channels or enzymes [35]. A number of chemical compounds, microorganisms, and acidic pectinases have been reported to induce resistance against plant diseases [11].…”
Section: Elicitation Of Plant Disease Resistancementioning
confidence: 99%
“…), microorganisms (chitin, glucans, etc. ), and G proteins which are bound to the receptors and act by activating or inactivating ion channels or enzymes [35]. A number of chemical compounds, microorganisms, and acidic pectinases have been reported to induce resistance against plant diseases [11].…”
Section: Elicitation Of Plant Disease Resistancementioning
confidence: 99%
“…In each column, mean followed by the same subscripted letter was not significantly different (p < 0.05) according to the Duncan's multiple range test It is observed that BITC production is highly affected by the addition of biotic elicitors. Therefore, elicitation offers an attractive strategy for increasing the secondary metabolite in vitro production [31] . This study showed that both chitosan and salicylic acid increased accumulation of BITC in callus culture of S. persicaover the control.…”
Section: Elicitationmentioning
confidence: 99%
“…Elicitors are mainly of three types; biotic, abiotic and physical. Elicitors can enhance or even induce the biosynthesis of certain metabolites (Goel et al 2011 ) .…”
Section: Elicitationmentioning
confidence: 99%